(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to assess the knowledge, attitudes, and practices regarding the prevention of hepatitis B virus transmission among health science students at Phenikaa University in 2024, as well as related factors. Methods: A cross-sectional study was conducted on 223 health science students at Phenikaa University. Data was collected using a self-administered questionnaire, which included general information and items assessing knowledge, attitudes, and practices related to hepatitis B virus transmission prevention. Results: The proportions of students demonstrating adequate knowledge, positive attitudes, and appropriate practices were 92.8%, 69.1%, and 88.3%, respectively. There was a statistically significant relationship between knowledge and attitudes with practice (p<0.05). Conclusion: The proportion of Phenikaa University health science students with correct knowledge, positive attitudes, and appropriate practices regarding hepatitis B virus transmission prevention was generally at a good to high level. The study indicates that students with good knowledge and attitudes are more likely to engage in effective preventive practices.